Segurança do paciente em clínicas de hemodiálise: protocolos operacionais padrão de cateteres venosos centrais e de fístula arteriovenosa - Souza, Carlota Rocha de Matos (2022)
Vascular access is extremely important for the quality of life of a person on hemodialysis (HD). Patients with chronic kidney disease have vulnerabilities and numerous risk factors for the development of adverse events (AEs). Effective application of standard operating protocols (SOP) by health professionals provides a safer environment for the HD patient. This study aimed to diagnose the implementation status of protocols for handling central venous catheters and arteriovenous fistulas in three hemodialysis clinics in the State of São Paulo, to coordinate with the responsible nurse technician and to assist in updating the current protocols according to the best clinical practices and to discuss with the nursing technicians of the participating clinics the main contents where gaps in learning and educational activity were identified. This is a quantitative and qualitative, cross-sectional study with an analytical purpose. Thirty-three nursing technicians from the clinics chosen by convenience freely participated. Data collection instruments were: sociodemographic questionnaire; document analysis of existing SOPs and field research to monitor the practical implementation of SOPs; a focus group implementation, with content analysis by Bardin. All quantitative analyzes were performed using Stata® statistical software, version 15.1. A significance level of 5% was considered. No statistical difference was observed between sociodemographic and work characteristics among professionals from different clinics. Regarding SOP, nursing technicians indicated that they knew what it is (94.0%) and what it is for (87.9%). Most employees mentioned they had received training (69.7%). In order to assess compliance with good practice protocols, an adequacy index was created consisting of six components, based on national and international guidelines/positions. Adequate performance was scored as one and inadequate performance was scored as zero. Analyzing the percentage of correct answers by component, it is noted that component 5 (Fistula care (AVF) during HD and AVF Intercurrences) was the one with the highest percentage of correct answers among the nursing staff of all the clinics evaluated (79 .7%). The component with the worst overall hit rate (42.7%) was the Disconnection of the patient with CVC (central venous catheter) using a valved connector. When analyzing the sum of the 6 components, an average of 45.1 points out of 81 possible was obtained, corresponding to 48.1% of correct answers in the average of the 3 clinics, but none of them individually reached an average of correct answers ≥ 80%, considering the index compliance and the fact that all had global rates < 70%, corresponds to unwanted assistance. The focus group allowed categorization into 5 main themes: technical operational failures due to inexperience, the meaning of standard operating procedures, gaps in knowledge and specific skills, inadequate inputs to the hemodialysis procedure and work overload and dehumanization. There was a great concern of nursing technicians regarding the patients comfort – physical and psychological. However, it is evident that they are subordinate to a diffuse hierarchical organization, without the support of political guidelines. The results of this paper indicate that, for effective implementation of SOPs, management interventions are necessary. Safe care depends on legislation compliance, continuing education, investment in quality inputs, oriented management towards patient safety, with a humanized look at the technical nursing team, and everyone needs to be involved in patient care. Basic measures prevent serious infections. It is intended that the good practices guide, the result of this study, be an instrument to support continuing education and bring improvements in the assistance quality in hemodialysis clinics